Mathematical modelling of the process of crest formation by the working body of the cultivator – dump type. Issue 1 (September 2020) - Algazin, D N; Kem, A A; Shevchenko, A P; Begunov, M A; Koval, V S
Abstract: The results of theoretical studies of the cultivator - dump type ridger are presented. The analysis of the forces acting on the working body is carried out. An expression is obtained for determining the second consumption of soil mass transported by a working body. The rational parameters of the working body are determined.